Capitalismo humanista como sistema efetivador do direito ao desenvolvimento - Pante, Giana (2022)
The present work aims to analyze whether within the capitalist economic scenario it is possible to promote development in line with the realization of human rights. It was found that the standards stipulated in the Federal Constitution are sufficient, in normative terms, to guarantee economic development in a humane way. However, it is clear that the change in the economic scenario, with capital now being seen as a characteristic element of private power without State intervention and the rise of neoliberalism, are impeding factors for constitutional dictates to be effectively implemented. in society. It was found that capitalism is not at all incompatible with the development and realization of human rights, but that a new way of conducting capitalism is necessary. Humanist Capitalism, based on anthropophilic human philosophy, demonstrated itself as a viable means of achieving development in a humane way and compatible with constitutional principles.